The Economic Tragedy of Proxy Wars : A look into the Spanish and Syrian Civil Wars - Al Hennawi, Žudi (2025)
With a particular focus on the Spanish Civil War (1936-1939) and the ongoing Syrian Civil War, this thesis explores the long-term economic consequences of proxy wars. It investigates the economic reforms implemented in Spain following its civil war and analyses how long it took for the economy to recover. Using Spain’s post-war recovery as a historical framework, the study applies a regression analysis to project Syria’s potential post-war economic path. The research tests the hypothesis that civil wars have severe and lasting economic consequences, often prolonging recovery. By comparing Spain’s historical experience, with Syria’s current situation, the thesis aims to provide insights into which factors may accelerate or hinder Syria’s economic recovery in the years ahead.